Twenty-year changes in mortality rates and underlying causes of death in patients with rheumatoid arthritis-associated interstitial lung disease. (3rd September 2021) - Gao, J; Xin, L; Guo, Q; Xu, K; Zhang, G; Yang, Y; Ma, D; Zhang, L
Abstract : Objectives : Despite recent advances in the treatment of rheumatoid arthritis (RA), few population-based studies have assessed the mortality rates and the underlying causes of death (UCDs) among patients with RA and RA-associated interstitial lung disease (RA-ILD). This study evaluated the trends in mortality rates, demographic characteristics, and UCDs among patients with RA-ILD. Method : Using data from death certificates (1999–2018) from the US Centers for Disease Control and Prevention Multiple Cause of Death files, we explored the trends in mortality rates and UCD for patients with RA and RA-ILD. Moreover, we examined the crude and age-standardized mortality rates (ASMRs) for such patients. Results : Among patients with RA or RA-ILD, ASMR variation decreased over 20 years. The ASMR ratio of RA-ILD to RA decreased by 5.84%. The ASMR for RA and RA-ILD stratified by gender or age group also decreased. The change in the ASMR ratio of RA-ILD to RA trended downwards in women and upwards in men. Arthropathies and ILD were the most frequent UCDs for RA-ILD, while arthropathies and ischaemic heart disease were the most frequent UCDs for RA. Conclusions : Although RA and RA-ILD presented a downward trend in mortality, RA combined with ILD may reduce life expectancy. Specifically, the mortality rate for patients with RA-ILD remained relatively stable during the study period when ILD was the UCD, suggesting the need for active prevention, early diagnosis, and effective management of RA-ILD.